Hot Wind to the Body Can Facilitate Vection Only When Participants Walk Through a Fire Corridor Virtually. (February 2021) - Yahata, Ryotaro; Takeya, Wataru; Seno, Takeharu; Tamada, Yasuaki
Vection has been reported to be enhanced by wind, as long as the wind is a normal temperature and not hot. However, here we report that a hot wind can facilitate vection, as long as it is natural and consistent with the visual stimulus. We created a fire-corridor stimulus that was consistent with a hot wind and a control stimulus composed of cubes, which were irrelevant to a hot wind. We compared the vection strength induced by a fire-corridor (fire condition) visual stimulus with that induced by geometric cubes (no-fire condition) visual stimulus. There were three wind type conditions: a normal temperature wind, hot wind, and no wind. The results showed that a normal temperature wind facilitated vection and that a hot wind (but not a normal wind) highly enhanced vection when a fire-corridor stimulus was presented. These results suggest that vection is highly affected and modulated by high-level cognitive processes.